Numerical simulation of condensation of sulfuric acid and water in a large two-stroke marine diesel engine. (1st February 2018) - Karvounis, Nikolas; Pang, Kar Mun; Mayer, Stefan; Walther, Jens Honoré
Highlights: The film condensation affects the total mass of acid vapor. The scavenging air humidity has a strong influence on the condensation of water. The total condensed sulfuric acid scales linearly with the fuel sulfur content. The present CFD model allows spatial analysis of the condensation. Abstract: In the present study, three-dimensional (3D) computational fluid dynamics simulations are performed to examine the process of sulfuric acid ( H 2 SO 4 ) and water ( H 2 O ) condensation in a large two-stroke marine diesel engine. A skeletal n-heptane chemical mechanism is coupled with a sulfur ( S ) subset to simulate the combustion process as well as the formation of sulfuric oxides ( SO x ) and H 2 SO 4 . The condensation process is simulated using a fluid film model which is coupled with the in-cylinder gas phase. Prior to the engine simulations, the fluid film condensation model is validated using the experimental data of sulfuric acid condensation rate in a laminar pipe flow. Next, the engine model is validated against the experimental sulfur dioxide ( SO 2 ) to sulfur trioxide ( SO 3 ) conversion obtained from the corresponding test engine. Both of the validation studies show a good agreement with the experimental data. The engine model is then utilized to simulate condensation for different operating conditions. The engine simulation results reveal that the fluid film has a significant effect on the total mass of sulfuric acid vapor and a marginal effect on the total mass of water vapor. A close to linear correlation is found between the fuel sulfur content and the total condensed mass of sulfuric acid. The level of humidity of the scavenging air does not affect the condensation of sulfuric acid considerably, relative to the humidity increase, but it has a high impact on water condensation. The study of the scavenging pressure level reveals a counter intuitive behavior where the condensation rates decrease with higher scavenging pressures due to the flow regime and flame size. Next, increasing the cylinder liner temperature decreases significantly the water condensation contrary to the sulfuric acid condensation which is marginally affected. The increase in lubricant film thickness results in a decrease for both the sulfuric acid and water condensation with a more pronounced reduction for water. Finally, a comparison between the high and low load operating conditions reveals a small drop in the total condensed mass of sulfuric acid and water for the low load conditions.